Pengaruh Flashcard Ekspresi Terhadap Perkembangan Kognitif Anak Usia Prasekolah - Saputri Indah Lestari; Ari Damayanti Wahyuningrum; Ari Dwi Sulaksono (Media Husada Journal Of Nursing Science, 2026)
Abstract The cognitive development of The cognitive development of preschool children is crucial, as this period is often referred to as the "golden age." However, a significant concern exists as 25% of children in Indonesia experience cognitive impairment. This issue is also observed at a local level; at Kemala Bhayangkari 10 Kindergarten, 12 out of 32 children were found to have problems with memory and concentration. To address this, one effective intervention for preschoolers is the use of flashcards. This study utilizes expression flashcards, a visual and engaging medium that can make learning enjoyable for children. The use of these flashcards aims to enhance children's intelligence by teaching them to recognize and imitate various facial expressions, understand their meaning, and apply them in their behavior. To examine the effect of using expression flashcards on the cognitive development of preschool children.This research methode used a quasi-experimental design with a pre-test and post-test control group. The research sample consisted of children aged 4-5 years at TK Kemala Bhayangkari 10. Data were collected through observation sheets and analyzed using a paired t-test. The result  use of expression flashcards on intervention group demonstrated a statistically significant increase in cognitive ability. The proportion of children categorized as 'poor' or 'sufficient' decreased, whereas the number of children in the 'good' category rose from 5 to 14 (p = 0.000). Conversely, the control group showed no significant improvement (p = 0.60). Keywords: expression flashcards, cognitive development, preschoolchildren.